2020
DOI: 10.1161/atvbaha.119.313658
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Determined ABO Blood Group and its Associations With Health and Disease

Abstract: Objective: To determine the spectrum of phenotypes linked to the ABO blood group system, using genetic determinants of the ABO blood group system. Approach and Results: We assessed the risk of 41 health and disease outcomes, and 36 linear traits associated with the ABO blood group system in the UK Biobank cohort. A total of 406 755 unrelated individuals were included in this study. Blood groups A, B, and O were determined based on allele … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
127
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(134 citation statements)
references
References 30 publications
5
127
2
Order By: Relevance
“…ABO blood types of participants were inferred through their genetic profiles. 5 Participants with blood type A had increased odds of at least one positive Covid-19 test relative to blood type O participants (P = 0.003), consistent with the previously-noted association (supplementary eTable 7). 6 However, no significant associations were identified when comparing Covid-19 positive inpatients to positive outpatients.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…ABO blood types of participants were inferred through their genetic profiles. 5 Participants with blood type A had increased odds of at least one positive Covid-19 test relative to blood type O participants (P = 0.003), consistent with the previously-noted association (supplementary eTable 7). 6 However, no significant associations were identified when comparing Covid-19 positive inpatients to positive outpatients.…”
Section: Resultssupporting
confidence: 84%
“…4 Dihydropyridine calcium channel blockers included amlodipine, felodipine, isradipine, nicardipine, and nifedipine. 5 Beta blockers included acebutolol, atenolol, bisoprolol, carvedilol, labetalol, metoprolol, nadolol, nebivolol, pindolol, and propranolol. 6 Thiazolidinediones included rosiglitazone, troglitazone, and pioglitazone.…”
Section: Copyright/license For Publicationmentioning
confidence: 99%
“…and a recessive inactive alleles. The association between ABO blood groups and infectious and non-infectious diseases has been widely explored (Groot et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it has been shown that blood type A is a risk factor for gastric cancer [9][10][11] while blood type O is a protective factor for atherosclerosis. [12][13][14] Cardiovascular diseases and cancers impact the lifespan significantly. Thus, the association between ABO blood types and human longevity has naturally been evaluated previously.…”
mentioning
confidence: 99%